Evaluación técnico financiera del sistema de levantamiento artificial ESPCP en un campo en el Valle Medio del Magdalena a partir de un análisis de fallas (2019)
The failures presented in the ESPCP equipment installed in the VMM field are analyzed in order to find the critical variables that most affect the survival of the equipment.Once the variables have been identified, by survival analysis, "safe" operation parameters are defined in order to meet the expectation of the proposed Run Life. After that, the operation parameters suggested in the work are applied to the 2 wells of the field that presented the highest number of failures, to evaluate the performance of the system. Finally, the decrease in current resources destined to cover guarantees due to equipment failures was estimated using the Net Present Value methodology.